Analysis of Informal Microfinance Institutions Structures in Relation to Performance in Tharaka South Subcounty, Kenya - Kaua, Caxton Gitonga; Thenya, Thuita; Mutune, Jane Mutheu (European Journal of Sustainable Development, 2020)
Informal microfinance is the delivery of financial services mainly to low income people outside the regulation of the monetary authority. Despite their importance in development, no studies have undertaken a detailed analysis of structures and performance in informal microfinance institutions. This study aims to analyze structures and performance in informal microfinance institutions in Tharaka South Sub County. It uses descriptive study design and multi stage sampling design. Data analysis was done using thematic, descriptive and Kendall’s tau-b correlation analysis. An informal microfinance performance index was developed using inductive and hierarchical approaches. The study found the informal microfinance institutions are marked by high performance which is determined by their structures. Moreover, the study deduced that informal microfinance is a key policy strategy for poverty alleviation, financial inclusion, gender equity and resilience building since participants mainly include women and other vulnerable groups. Keywords: Capital, Livelihoods, Informal, Microfinance, Performance, social